O neoliberalismo de terceira via e o empresariamento da Educação: apontamentos sobre a relação entre Itaú Social e o IEA/USP - Hanna, Luiza Kouri (Universidade Federal de São Carlos, 2023)
The present study is the result of explanatory and qualitative research, with a bibliographic and documentary view, which has aimed to analyze the third-way neoliberalism and the private administration of Brazilian public education, shedding light on the relation between Itaú Social and the Instituto de Estudos Avançados da USP (Advanced Studies Institute/ IEA– University of São Paulo), as a mean to exemplify the discussion nowadays. Therefore, a bibliographical review of the critical authors in the debate in question was made, as well as a documentary analysis of the Cadernos MARE, the Plano Diretor da Reforma do Aparelho do Estado (PDRAE), and the production of Cátedra Alfredo Bosi da Educação Básica (a partnership between Itaú Social and IEA/USP). The result shows that Brazilian private management was, and still is, successful in its entrepreneurship in formulating public education policies and teacher training, through the process of professionalization of education workers, who previously had their image built as an obstacle to the Reform and afterward as agents of the new hegemonic pedagogy.
Third way neoliberalism and the entrepreneurship of Education: notes on the relationship between Itaú Social and the IEA/USP
Keywords: Estado e Terceiro Setor; Empresariamento da Educação; Formação de Professores; State and Third Sector; Education Entrepreneurship; Teacher Training; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO